2013
DOI: 10.29333/ejgm/82209
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Levels in Patients with Rickets

Abstract: Rickets is a common metabolic bone disease in infants. The predominant cause of rickets is vitamin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…Gender and age were not related to development of rickets in studied children. This finding agreed with Tom et al , and Yasar Sen et al, who reported no relation between rachitic infants and age or sex [8, 9]. Rachitic children in our study found to have lower length values and lower mean body weight than non-rachitic children and this agrees with the study of Graff et al [11], and Rooze et al [12], but, this was not the same for Yasar Sen et al , as the difference between rachitic children and controls regarding their weight and height was insignificant [9].…”
Section: Discussionsupporting
confidence: 92%
“…Gender and age were not related to development of rickets in studied children. This finding agreed with Tom et al , and Yasar Sen et al, who reported no relation between rachitic infants and age or sex [8, 9]. Rachitic children in our study found to have lower length values and lower mean body weight than non-rachitic children and this agrees with the study of Graff et al [11], and Rooze et al [12], but, this was not the same for Yasar Sen et al , as the difference between rachitic children and controls regarding their weight and height was insignificant [9].…”
Section: Discussionsupporting
confidence: 92%